Determinants of Financial Performance in Banking Securitization in Southeast Asianv - Gos Ishak; Farah Margaretha Leon; Bahtiar Usman (Iapa Proceedings Conference, 2020)
The purpose of this paper is to examine the effect of financial performance in banking securitization in Southeast Asian. In particular, the authors examine two important issues. First, the ABS (Asset-Backed Securities) effect on Return on Assets (ROA) as indicators of firm profitability. Second, bank securitization improved profitability by securitizing its portfolio loans to investors to get liquidity. The authors used a sample of 12 commercial banks in Southeast Asian Countries (including Indonesia, Singapore, Thailand, Malaysia, and the Philippines). A data panel regression model was used from 1998 to 2018. The results show that ABS has found a significant positive on ROA as an indicator of firm profitability. On the other hand, ABS has a negative relationship with the size as a moderating variable on ROA. Furthermore, banks can liquidate loans to finance the liquidity they need without dependence on traditional sources of funds (deposits, savings, and current accounts). In addition, securitization improved financial ratios such as ROA, Size, and reduces banks securitization’s default risk